ENGLISH FOR INDONESIAN: âDESIGNING CURRICULUM DEVELOPMENT BASED ON GENDER EQUALITYâ - Laylisna, Novi Nur (Jurnal al Hikmah, 2016)
Education is a process that never has ending during human life. It is also the human right as the long-life pass. In Indonesia, each citizen has the same right in having education service as the Governance program. What the most crucial subject that studied in school of education is English Subject. Till this time, that subject is not un-easy course because of the term of Foreign Language. In other hand, there are also found some topic that not represents the right for woman and man in the education service, as like gender bias in some textbook, teacherâs interaction and discrimination. Then, how to make English for general learners could be the of curriculum design that proposed for students. It is very complex processes and need some supported element to be existed. What is going to be the alternative curriculum is gender-based curriculum. There is no gender gap in all aspect of curriculum design. Keywords: Education, English in Indonesia, Curriculum design, Gender-based